2011
DOI: 10.1371/journal.pone.0025613
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical Architecture of the Central Complex Related to Its Function in the Control of Grasshopper Acoustic Communication

Abstract: The central complex selects and coordinates the species- and situation-specific song production in acoustically communicating grasshoppers. Control of sound production is mediated by several neurotransmitters and modulators, their receptors and intracellular signaling pathways. It has previously been shown that muscarinic cholinergic excitation in the central complex promotes sound production whereas both GABA and nitric oxide/cyclic GMP signaling suppress its performance. The present immunocytochemical and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 73 publications
(148 reference statements)
1
23
0
Order By: Relevance
“…Interestingly, a recent metaanalysis strongly suggests that the CX is deeply homologous to the mammalian basal ganglia (Strausfeld and Hirth, 2013). Moreover, the CX is heavily invested in GABAergic (inhibitory) receptors as well as receptors for numerous neuromodulators, including dopamine (Homberg et al, 1999;Kahsai and Winther, 2011;Kunst et al, 2011;Kahsai et al, 2012).…”
Section: Research Articlementioning
confidence: 99%
“…Interestingly, a recent metaanalysis strongly suggests that the CX is deeply homologous to the mammalian basal ganglia (Strausfeld and Hirth, 2013). Moreover, the CX is heavily invested in GABAergic (inhibitory) receptors as well as receptors for numerous neuromodulators, including dopamine (Homberg et al, 1999;Kahsai and Winther, 2011;Kunst et al, 2011;Kahsai et al, 2012).…”
Section: Research Articlementioning
confidence: 99%
“…Evidence for polarization-independent visual functions largely originates from behavioral experiments on mutant and transgenic flies (Drosophila melanogaster) with defects in parts of the CC. These studies suggest that CC neurons detect the orientation and elevation of edges (Liu et al, 2006), play a role in visually mediated spatial orientation memory (Neuser at al., 2008) and place memory (Ofstad et al, 2011), and are involved in the visual control of gap-crossing behavior . Data from neuronal recordings substantiating these results are missing, however, except for a single study reporting responses to moving bars in the CC of flesh flies (Phillips-Portillo, 2012).…”
Section: Visual Integration In the CCmentioning
confidence: 99%
“…5). Kunst et al (2011) showed that activation of PoU1 neurons in grasshoppers inhibits the generation of calling songs. This further supports the shut-off hypothesis.…”
Section: Response Specificity and Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…GABA is a major inhibitory transmitter in the insect brain (Buckingham, Biggin, Sattelle, Brown, & Sattelle, ; Lummis, ). In all species studied, including grasshoppers (Homberg, Vitzthum, Müller, & Binkle, ; Kunst, Pförtner, Aschenbrenner, & Heinrich, ), the house cricket (Strambi et al, ), the tobacco hawk moth (Homberg, Kingan, & Hildebrand, ), the American cockroach (Blechschmidt, Eckert, & Penzlin, ), the honeybee (Mota et al, ; Schäfer & Bicker, ), and two species of flies (Hanesch et al, ; Meyer, Matute, Streit, & Nässel, ), the CBL showed dense GABA immunostaining. Detailed analysis in the locust Schistocerca gregaria , the fly Drosophila melanogaster , and the moth Manduca sexta identified tangential neurons of the CBL (termed TL neurons in locusts, R neurons in flies) to be immunostained.…”
Section: Introductionmentioning
confidence: 99%